Inhibition of complement-mediated cytolysis by the terminal complement inhibitor of herpesvirus saimiri. - Rother, R P (1994)
Herpesvirus saimiri (HVS) is a lymphotropic herpesvirus that induces T-cell transformation in vitro and causes lymphomas and leukemias in New World primates other than its natural host, the squirrel monkey. Nucleotide sequence analysis of the HVS genome revealed two open reading frames with significant homology to genes for human complement regulatory molecules. One of these genes encodes a predicted protein (designated HVSCD59) with 48% amino acid sequence identity to the human terminal complement regulatory protein CD59 (HuCD59). The CD59 homolog from squirrel monkey (SMCD59) was cloned, and the corresponding amino acid sequence showed 69% identity with HVSCD59. BALB/3T3 cells stably expressing HVSCD59, SMCD59, or HuCD59 were equally protected from complement-mediated lysis by human serum. However, only HVSCD59-expressing cells were effectively protected from complement-mediated lysis when challenged with rat serum, suggesting that HVSCD59 was less species restrictive. The complement regulatory activity of HVSCD59 and SMCD59 occurred after C3b deposition, indicating terminal complement inhibition. Treatment of BALB/3T3 stable transfectants with phosphatidylinositol-specific phospholipase C prior to complement attack decreased the complement regulatory function of HVSCD59, suggesting cell surface attachment via a glycosyl-phosphatidylinositol anchor. Cells expressing HVSCD59 effectively inhibited complement-mediated lysis by squirrel monkey serum in comparison with SMCD59-expressing cells. Finally HVSCD59-specific transcripts were detected in owl monkey cells permissive for lytic HVS replication but not in T cells transformed by HVS, which failed to produce virions. These data are the first to demonstrate a functional, virally encoded terminal complement inhibitor and suggest that HVSCD59 represents a humoral immune evasion mechanism supporting the lytic life cycle of HVS.